Pteropods counter mechanical damage and dissolution through extensive shell repair - Victoria L. Peck (Nature Portfolio, 2018)
Sea butterflies, or pteropods, are often presented as being at threat from ocean acidification on account of their fragile shells being susceptible to dissolution. Here the authors show that pteropods are able to perform extensive repair to damaged shells, suggesting they may not be as vulnerable as previously thought.